Estimating shadow price for symbiotic nitrogen and technical efficiency for legume‐based conservation agriculture in Malawi. (28th May 2017) - Khataza, Robertson R. B.; Hailu, Atakelty; Kragt, Marit E.; Doole, Graeme J.
Abstract : Determining the value of legumes as soil fertility amendments can be challenging, yet this information is required to guide public policy and to incentivise prescribed land‐management practices such as conservation agriculture. We use a directional input distance function (DIDF) to estimate shadow prices for symbiotic nitrogen and the technical efficiency for mixed maize‐legume production systems in Malawi. The shadow prices reflect the trade‐off between fertiliser nitrogen and symbiotic nitrogen required to achieve a given quantity of output. Our results reveal considerable technical inefficiency in the production system. The estimated shadow prices vary across farms and are, on average, higher than the reference price for commercial nitrogen. The results suggest that it would be beneficial to redesign the current price‐support programs that subsidise chemical fertilisers and indirectly crowd‐out organic soil amendments such as legumes.